Architecture Design and Key Technologies Analysis of LEO Satellite Mega-Constellations - Zihe GAO; Haipeng YAO; Lei ZHANG; Yulin SHI; Fu WANG; Ying TAO (天地一体化信息网络)
The large number of network elements in the mega-constellations pose a severe challenge to the existing network architecture and technical system.Based on the concept and characteristics of constellation architecture, combined with the development of domestic and foreign satellite constellations and technology prediction, a multi-layer and multi-domain hybrid intelligent cooperative network architecture was proposed, which consist of four layers (perception plane, data plane, control plane, intelligent management plane) and three layers (resource layer, transport layer, service layer) , the architecture of constellation network management and control, technology reference model and protocol architecture were designed.At the same time, accorded to the construction and development trend of constellation, this paper expounded and analyzed the evolution trend of the key technologies, such as constellation network addressing and routing, network robust agile guarantee, differentiated service bearing, end-to-end reliable transmission, etc.The research results could support the development and construction of LEO giant constellation network in our country.